Impelementasi Kebijakan Penanggulangan HIV/AIDS pada Dinas Kesehatan Kabupaten Melawi - Endang Susilawati (JPASDEV : Journal of Public Administration and Sociology of Development, 2020)
ABSRACTAbstractPolicy implementation of HIV/AIDS Countermeasures in the Melawi Regency Health Office. The aim of this research is to describe and analyze the process of implementing HIV/AIDS policy in Melawi Regency in terms of communication, resources, disposition and bureacucratic structure. The research subjects include the Head of Health Office, Secretary of Health Office, the Division and Section Heads, Technical staff managing HIV/AIDS, Hospital director including the VCT Team and Private Hospitals, 11 Regency Public Health Center Heads, VCT Staff at the Nanga Pinoh Public Health Center, community Leaders, PLWHA and Key Population. Research results indicate that the implementation of HIV/AIDS countermeasures in Melawi Regency has not been as expected. It is observed from the communication stage that has not been well established in the response to the aforementioned illness, the inadequate resources of supporing infrastructure and funds that have not been focused. Human Resources have not been trained. Data collection, program managers, and the role disposisition of officers are not optimal. The bureaucracy structure has not been prepared properly, including SOP and SPM. This is observed from the different perceptions of the officers managing the HIV/AIDS program. The application system has not been well apprehended due to the absence of technical staff and PLHIV/key population unwilling to volunteer to be treated. Key words : The Implementation Policy, HIV/AIDS Countermeasures.